Identity-based roaming protocol with anonymity for heterogeneous wireless networks - JIANG Qi1; MA Jian-feng1; LI Guang-song1; LIU Hong-yue1 (Tongxin xuebao)
The security flaws of an identity-based authentication model were analyzed.The scheme failed to achieve entity authentication due to identity impersonation attack.Then,an improved authentication scheme was proposed to realize anonymous roaming in heterogeneous wireless networks.The authentication scheme improves the original one in two aspects.Firstly,the scheme remedies the security flaws and is provably secure in the CK model.Secondly,the scheme simplifies the protocol interaction and it is more efficient.